Electrolyte composition, secondary battery, battery module, battery pack, and electric device

CN119213600APending Publication Date: 2024-12-27CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202280096226.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing liquid electrolytes and all-solid electrolytes have problems with short circuit risk and poor interface contact in secondary batteries, and cannot meet the application needs of the new generation of electrochemical systems.

Method used

Develop a non-Newtonian fluid electrolyte composition that undergoes mechanical thixotropy under the action of external force, transforming from a flowable state to a solid state, improving the impact resistance and safety of the battery, and achieving minimal Electrolyte ohmic resistance and interface resistance, improving the assembly process.

Benefits of technology

It effectively improves the short-circuit safety and impact resistance of the battery, reduces the gas production rate and expansion rate of the battery, simplifies the assembly process, and improves cycle performance and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119213600A_ABST
    Figure CN119213600A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte composition, a secondary battery, a battery module, a battery pack and an electric device. The electrolyte composition is a non-Newtonian fluid electrolyte composition. The impact resistance and the safety of the battery can be improved through mechanical thixotropy under a certain external force.
Need to check novelty before this filing date? Find Prior Art

Description

Electrolyte composition, secondary battery, battery module, battery pack and electrical device Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to an electrolyte composition, a secondary battery, a battery module, a battery pack, and an electrical device. Background Art

[0002] In recent years, secondary batteries have been widely used in energy storage systems such as hydropower, thermal, wind, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and other fields. With the widespread use of secondary batteries, higher requirements have been placed on their performance and safety.

[0003] At present, liquid electrolytes and all-solid-state electrolytes are the two most commonly used electrolytes in batteries. However, liquid electrolytes are prone to generate dendrites at the negative electrode during the cycle, causing battery short circuit and causing safety problems. All-solid-state electrolytes are difficult to form excellent interface contact with the electrode, and neither can meet the application needs of the new generation of electrochemical systems.

[0004] Summary of the Invention

[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide an electrolyte composition that can improve the impact resistance and safety of the battery by undergoing mechanical thixotropy under a certain external force.

[0006] In a first aspect of the present application, an electrolyte composition is provided, wherein the electrolyte composition is a non-Newtonian fluid electrolyte composition.

[0007] Non-Newtonian fluid electrolyte compositions can undergo mechanical thixotropy under certain external forces, transforming from a flowable state to a solid state, effectively improving the battery's short-circuit safety and impact resistance. Furthermore, compared to other quasi-solid-state and liquid electrolytes, non-Newtonian fluid electrolyte compositions can achieve minimal electrolyte ohmic resistance and interfacial resistance at lower stacking pressures, improving the battery assembly process.

[0008] After the electrolyte composition is stirred by rotating a 62# or 64# rotor of a Dveslvtjo rotary viscosity tester at a speed of 12 rpm for 10 seconds at 25° C., the viscosity of the electrolyte composition is 1000 mPa·s to 50000 mPa·s.

[0009] The non-Newtonian fluid electrolyte composition has a high viscosity. Compared with a battery with a liquid electrolyte of similar composition, the non-Newtonian fluid electrolyte composition can effectively suppress the gas production of the battery through the high viscosity, thereby improving the cycle performance of the battery.

[0010] In any embodiment, after the electrolyte composition is stirred at 12 rpm for 10 minutes using a Dveslvtjo rotary viscometer 62# or 64# rotor at 25°C, the viscosity of the electrolyte composition increases by more than 100 mPa·s compared to its viscosity after 10 seconds tested under the same conditions.

[0011] The non-Newtonian electrolyte composition does not satisfy Newton's viscosity law, that is, the shear stress and shear strain rate have a nonlinear relationship. The non-Newtonian electrolyte composition in this application is a shear thickening liquid, and its viscosity increases with increasing shear rate or shear time.

[0012] In any embodiment, the loss factor of the non-Newtonian fluid electrolyte composition after mechanical thixotropy decreases by more than 10% compared to the loss factor before mechanical thixotropy.

[0013] Non-Newtonian fluid electrolytes have mechanical thixotropic properties. Under the impact of external forces such as needle puncture or extrusion, the non-Newtonian fluid electrolyte composition changes from a fluid state to a solid state. The phase change causes its loss factor to decrease. The decrease rate of the loss factor of the non-Newtonian fluid electrolyte composition exceeds 10%, that is, the storage modulus is significantly increased, thereby effectively improving the safety and impact resistance of the battery in the event of accidents such as needle puncture.

[0014] In any embodiment, the non-Newtonian fluid electrolyte composition comprises one of an organic solvent and an ionic liquid, an electrolyte salt, and suspended particles.

[0015] Non-Newtonian fluid electrolyte compositions comprising an electrolyte salt, an ionic liquid, and suspended particles, or comprising an electrolyte salt, an organic solvent, and suspended particles, exhibit excellent safety and impact resistance. Furthermore, these non-Newtonian fluid electrolyte compositions achieve minimal electrolyte ohmic resistance and interfacial resistance at low stacking pressures, simplifying the battery assembly process.

[0016] In any embodiment, the non-Newtonian fluid electrolyte composition further comprises a polymer.

[0017] The introduction of polyethylene oxide into the non-Newtonian fluid electrolyte composition is beneficial to improving the cycle performance of the battery, reducing the battery expansion rate, reducing the gas production rate, and improving the safety of the battery.

[0018] In any embodiment, the electrolyte salt comprises a sodium salt, and the sodium salt comprises one or more of sodium chloride, sodium bromide, sodium nitrate, sodium perchlorate, sodium hexafluorophosphate, sodium acetate, sodium trifluoroacetate, sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide, and optionally comprises one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide.

[0019] The sodium salts described above are beneficial for improving the safety and impact resistance of non-Newtonian fluid electrolyte compositions, improving the cycle performance of batteries, reducing the gas production rate of batteries, and achieving the stacking pressure required to minimize the electrolyte ohmic resistance and interfacial resistance, thereby improving battery safety and the battery assembly process. The sodium salts may optionally include one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide, which further improves the cycle performance of the batteries.

[0020] In any embodiment, the organic solvent comprises one or more of an ether organic solvent, an ester organic solvent, and a sulfur-containing organic solvent, and comprises one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, fluoroethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, and dimethyl sulfoxide, and optionally comprises ethylene glycol dimethyl ether.

[0021] These organic solvents help improve the safety and impact resistance of non-Newtonian electrolyte compositions, reduce the stacking pressure required to minimize the electrolyte ohmic resistance and interfacial resistance, and improve the battery assembly process. The organic solvent optionally includes ethylene glycol dimethyl ether, which further improves the safety and impact resistance of the non-Newtonian electrolyte composition, significantly enhances the battery's cycling performance, significantly reduces the battery's gas production rate, and improves battery safety.

[0022] In any embodiment, the ionic liquid comprises one or more of 1-butyl-3-methylimidazole chloride, 1-alkyl-3-methylimidazole tetrafluoroboric acid, N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide, 5-azonia spiro[4,4]nonane hexafluorophosphate, trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide, and tetrabutylphosphine hexafluorophosphate, and optionally comprises one or more of N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)amide and trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide.

[0023] The above-mentioned ionic liquid is beneficial for improving the safety and impact resistance of the non-Newtonian fluid electrolyte composition, reducing the stacking pressure of the battery when the electrolyte ohmic resistance and interface resistance are minimized, and improving the battery assembly process. Controlling the ionic liquid to optionally include one or more of N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide and trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide is beneficial for further improving the safety and impact resistance of the non-Newtonian fluid electrolyte composition, greatly improving the cycle performance of the battery, significantly reducing the battery's gas production rate and achieving the stacking pressure when the electrolyte ohmic resistance and interface resistance are minimized, improving the battery safety, and improving the battery assembly process.

[0024] In any embodiment, the polymer comprises polyethylene oxide, polyethylene glycol, polyvinyl pyrrolidone, polymethyl methacrylate, polyvinylidene fluoride, polyvinyl alcohol, polyacrylamide, and optionally comprises one or more of polyethylene oxide and polyethylene glycol.

[0025] The aforementioned polymers are beneficial for improving the safety and impact resistance of non-Newtonian fluid electrolyte compositions, as well as reducing the battery's gas production rate and the stacking pressure required to minimize the electrolyte's ohmic resistance and interfacial resistance, thereby enhancing battery safety and improving the battery assembly process. The polymers can optionally include one or more of polyethylene oxide and polyethylene glycol, further improving the battery's cycling performance, significantly reducing the stacking pressure required to minimize the electrolyte's ohmic resistance and interfacial resistance, and improving the battery assembly process.

[0026] In any embodiment, the suspended particles include one or more of fumed silica, aluminum oxide, sodium oxide, lithium oxide, sodium fluoride, lithium fluoride, and polyurethane, and optionally include one or more of fumed silica, sodium oxide, and lithium oxide.

[0027] These suspended particles improve the safety and impact resistance of non-Newtonian electrolyte compositions, reduce the stacking pressure required to minimize the electrolyte ohmic resistance and interfacial resistance, and improve the battery assembly process. The suspended particles can optionally contain one or more of fumed silica, sodium oxide, and lithium oxide, further improving the battery's cycling performance, significantly reducing the battery's gas production rate, and enhancing battery safety.

[0028] In any embodiment, the electrolyte salt comprises one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide; the organic solvent comprises ethylene glycol dimethyl ether; the ionic liquid comprises one or more of N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide and trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide; the polymer comprises one or more of polyethylene oxide and polyethylene glycol; and the suspended particles comprise one or more of fumed silica, sodium oxide, and lithium oxide.

[0029] The selection of the above-mentioned electrolyte salt, organic solvent, ionic liquid, polymer and suspended particles is beneficial to improving the cycle performance of the battery.

[0030] In any embodiment, the electrolyte salt includes one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide, the organic solvent includes ethylene glycol dimethyl ether, and the suspended particles include one or more of fumed silica, sodium oxide, and lithium oxide.

[0031] The above-mentioned non-Newtonian fluid electrolyte composition comprising electrolyte salt, organic solvent and suspended particles is beneficial to improving the safety and impact resistance of the non-Newtonian fluid electrolyte composition, improving the cycle performance of the battery, and reducing the gas production rate of the battery and achieving the stacking pressure when the electrolyte ohmic resistance and interface resistance are minimized, thereby improving the safety of the battery and improving the battery assembly process.

[0032] In any embodiment, the electrolyte salt includes one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide, the organic solvent includes ethylene glycol dimethyl ether, the polymer includes one or more of polyethylene oxide and polyethylene glycol, and the suspended particles include one or more of fumed silica, sodium oxide, and lithium oxide.

[0033] The above-mentioned non-Newtonian fluid electrolyte composition comprising electrolyte salt, organic solvent, polymer and suspended particles is beneficial to improving the safety and impact resistance of the non-Newtonian fluid electrolyte composition, improving the cycle performance of the battery, and reducing the gas production rate of the battery and achieving the stacking pressure when the electrolyte ohmic resistance and interface resistance are minimized, thereby improving the safety of the battery and improving the battery assembly process.

[0034] In any embodiment, the electrolyte salt comprises one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide; the ionic liquid comprises one or more of N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide and trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide; and the suspended particles comprise one or more of fumed silica, sodium oxide, and lithium oxide.

[0035] The above-mentioned non-Newtonian fluid electrolyte composition comprising electrolyte salt, ionic liquid and suspended particles is beneficial to improving the safety and impact resistance of the non-Newtonian fluid electrolyte composition, reducing the stacking pressure of the battery when the electrolyte ohmic resistance and interface resistance are minimized, and improving the battery assembly process.

[0036] In any embodiment, the electrolyte salt comprises one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide; the ionic liquid comprises one or more of N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide and trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide; the polymer comprises one or more of polyethylene oxide and polyethylene glycol; and the suspended particles comprise one or more of fumed silica, sodium oxide, and lithium oxide.

[0037] The above-mentioned non-Newtonian fluid electrolyte composition comprising electrolyte salt, ionic liquid, polymer and suspended particles is beneficial to improving the safety and impact resistance of the non-Newtonian fluid electrolyte composition, reducing the stacking pressure of the battery when the electrolyte ohmic resistance and interface resistance are minimized, and improving the battery assembly process.

[0038] In any embodiment, based on the total mass of the non-Newtonian fluid electrolyte composition, the mass content of the electrolyte salt is 5% to 20%, the mass content of the organic solvent is 20% to 60%, the mass content of the ionic liquid is 20% to 60%, the mass content of the polymer is 0% to 40%, and the mass content of the suspended particles is greater than 0 and less than or equal to 20%.

[0039] Controlling the appropriate mass content of electrolyte salts, organic solvents, ionic liquids, polymers, and suspended particles is beneficial for improving the safety and impact resistance of non-Newtonian fluid electrolyte compositions, enhancing battery cycle performance, reducing battery gas production rates, and achieving the stacking pressure required to minimize electrolyte ohmic resistance and interfacial resistance, thereby improving battery safety and assembly processes. This enhances interfacial stability while ensuring the diffusion of metal ions.

[0040] In any embodiment, the non-Newtonian fluid electrolyte composition has a compressive strength of 35 kN to 200 kN.

[0041] The non-Newtonian fluid electrolyte composition has suitable extrusion strength, which is beneficial to improving its impact resistance.

[0042] A second aspect of the present application provides a secondary battery comprising a positive electrode sheet and the non-Newtonian fluid electrolyte composition described in any embodiment.

[0043] The secondary battery has excellent cycle performance.

[0044] In any embodiment, the secondary battery includes at least one of a lithium battery and a sodium battery.

[0045] In any embodiment, the secondary battery is a negative electrode-free sodium battery having high energy density.

[0046] In any embodiment, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes at least one of a transition metal layered oxide, a polyanion compound, and a Prussian blue compound, including NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2、Na(Cu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 )O2、Na 2 / 3 Ni 1 / 6 Mn 2 / 3 Cu 1 / 9 Mg 1 / 18 O2, Na4Fe3(PO4)2P2O7, NaFePO4, Na3V2(PO4)3, Na 1.9 One or more of CoFe(CN)6, Na2NiFe(CN)6, and NaMnFe(CN)6.

[0047] The above-mentioned positive electrode active materials can all make the battery have excellent cycle performance and safety.

[0048] In any embodiment, the surface of the positive electrode active material has a coating layer, and the coating layer includes one or more of carbon material, ZrO2, TiO2, polyaniline, polypyrrole, poly (3,4-ethylenedioxythiophene), aluminum oxide, zinc oxide, titanium oxide, zirconium oxide, magnesium oxide, silicon oxide, lanthanum oxide, sodium fluoride, lithium fluoride and aluminum fluoride, and the carbon material includes one or more of amorphous carbon, graphite, and graphene.

[0049] The surface of the positive electrode active material has a coating layer, which is more conducive to improving the cycle performance, greatly reducing the gas production rate of the battery, and improving the safety of the battery.

[0050] A third aspect of the present application provides a battery module, comprising the secondary battery according to the second aspect of the present application.

[0051] A fourth aspect of the present application provides a battery pack, comprising the secondary battery of the second aspect of the present application or the battery module of the third aspect of the present application.

[0052] A fifth aspect of the present application provides an electrical device comprising at least one of the secondary battery of the second aspect of the present application, the battery module of the third aspect of the present application, and the battery pack of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application;

[0054] FIG2 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG1 ;

[0055] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application;

[0056] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application;

[0057] FIG5 is an exploded view of the battery pack according to an embodiment of the present application shown in FIG4 ;

[0058] FIG6 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.

[0059] Description of reference numerals:

[0060] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION

[0061] Below, the embodiments of the electrolyte composition, secondary battery, battery module, battery pack and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0062] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0063] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0064] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0065] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0066] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0067] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0068] Currently, liquid electrolytes and all-solid-state electrolytes face numerous challenges. However, quasi-solid-state electrolytes have attracted the attention of researchers because they possess both liquid components and a certain geometric shape and strength, combining the advantages of both liquid and all-solid-state electrolytes. Their mechanical properties are crucial for maintaining the structural stability of the electrolyte during charge / discharge cycles. Therefore, it is necessary to develop an electrolyte that combines excellent mechanical properties with the advantages of quasi-solid-state electrolytes to meet the application needs of the next generation of electrochemical systems.

[0069] [Electrolyte composition]

[0070] Based on this, the present application proposes an electrolyte composition, which is a non-Newtonian fluid electrolyte composition.

[0071] In this article, non-Newtonian fluid refers to a fluid whose rheological properties do not satisfy Newton's experimental law of viscosity, that is, the relationship between shear stress and shear rate of the fluid is not linear.

[0072] Non-Newtonian fluid electrolyte compositions can undergo mechanical thixotropy under certain external forces, transforming from a flowable state to a solid state, effectively improving the battery's short-circuit safety and impact resistance. Furthermore, compared to other electrolytes with higher viscosities, non-Newtonian fluid electrolyte compositions can achieve minimal electrolyte ohmic resistance and interfacial resistance at lower stacking pressures, improving the battery assembly process.

[0073] In some embodiments, after the electrolyte composition is stirred at 12 rpm for 10 seconds using a Dveslvtjo rotary viscometer 62# or 64# rotor at 25° C., the viscosity of the electrolyte composition is 1000 mPa·s to 50000 mPa·s.

[0074] In some embodiments, after the electrolyte composition is stirred at 12 rpm for 10 seconds by a Dveslvtjo rotary viscometer 62# or 64# rotor at 25°C, the upper or lower limit of the viscosity of the electrolyte composition may be optionally 1000 mPa·s, 2000 mPa·s, 3000 mPa·s, 4000 mPa·s, 5000 mPa·s, 6000 mPa·s, 7000 mPa·s, 8000 mPa·s, 9000 mPa·s, 10000 mPa·s, 11000 mPa·s, 12000 mPa·s, 13000 mPa·s, 14000 mPa·s, 15000 mPa·s, 16000 mPa·s, 17000 mPa·s, 18000 mPa·s, ·s, 8000mPa·s, 9000mPa·s, 10000mPa·s, 12000mPa·s, 14000mPa·s, 16000mPa·s, 18000mPa·s , 20000mPa·s, 25000mPa·s, 30000mPa·s, 35000mPa·s, 40000mPa·s, 45000mPa·s or 50000mPa·s.

[0075] In this article, the viscosity of the non-Newtonian fluid electrolyte composition was tested using a Brookfield Dveslvtjo rotational viscometer. The test conditions were a temperature of 25°C, a time of 10 seconds, a 64# rotor for measuring viscosities not less than 2000 mPa·s, and a 62# rotor for measuring viscosities less than 2000 mPa·s, with a rotor speed of 12 rpm. Three parallel measurements were performed, and the average value was taken. Compared to batteries with liquid electrolytes of similar composition, non-Newtonian fluid electrolyte compositions can effectively suppress battery gas production through their high viscosity, thereby improving the battery's cycle performance.

[0076] In some embodiments, after the electrolyte composition is stirred at 12 rpm for 10 minutes using a Dveslvtjo rotary viscometer 62# or 64# rotor at 25°C, the viscosity of the electrolyte composition increases by more than 100 mPa·s compared to its viscosity after 10 seconds tested under the same conditions.

[0077] In some embodiments, after the electrolyte composition is rotated and stirred at a speed of 12 rpm for 10 minutes by a Dveslvtjo rotary viscosity tester 62# or 64# rotor at 25°C, the viscosity of the electrolyte composition compared to its viscosity after testing under the same conditions for 10 seconds may be increased by 100 mPa·s, 300 mPa·s, 500 mPa·s, 700 mPa·s, 900 mPa·s, 1000 mPa·s, 1200 mPa·s, 1400 mPa·s, 1600 mPa·s, 1800 mPa·s, 2000 mPa·s, 2200 mPa·s, 2400 mPa·s, 2600 mPa·s, 2800 mPa·s or 3000 mPa·s.

[0078] A non-Newtonian electrolyte composition does not satisfy Newton's viscosity law, i.e., shear stress and shear strain rate have a nonlinear relationship. In this context, a non-Newtonian electrolyte composition is a shear-thickening liquid, and its viscosity increases with increasing shear rate or shear time.

[0079] In some embodiments, the loss factor of the non-Newtonian fluid electrolyte composition after mechanical thixotropy decreases by more than 10% compared to the loss factor before mechanical thixotropy.

[0080] In this article, mechanical thixotropy refers to the transition of the electrolyte composition from a flowable state to a solid state by applying a certain external force to the electrolyte composition.

[0081] In some embodiments, mechanical thixotropy of the electrolyte composition is achieved by acupuncture. As an example, a high-speed rail tensile tester and acupuncture fixture are used to acupuncture a battery based on the electrolyte composition. A puncture tester uses a 1 mm diameter needle at a speed of 6 mm / min to a puncture depth of 2 mm. In some embodiments, mechanical thixotropy of the electrolyte composition is achieved by extrusion. As an example, a semi-cylindrical extrusion plate with a radius of 75 mm is used to extrude the battery perpendicular to the direction of the battery electrode at an extrusion speed of 60 mm / min.

[0082] As used herein, the term "loss factor" refers to the ratio of loss modulus to storage modulus.

[0083] In this article, the loss factor of a non-Newtonian electrolyte composition can be tested using methods known in the art. For example, a sample is cut into a disc with a diameter of 20 mm and a thickness of 1 mm. The testing instrument is a Haake rheometer at a temperature of 25°C. The strain sweep range is 0.1% to 1000% at a fixed frequency of 1 Hz. The storage modulus (G′) and loss modulus (G″) are obtained, respectively. The loss factor (tan δ) is calculated using the formula tan δ = G″ / G′.

[0084] Herein, the term "decline rate" = (loss factor before mechanical thixotropy - loss factor after mechanical thixotropy) / loss factor before mechanical thixotropy.

[0085] In some embodiments, the decrease rate of the loss factor of the non-Newtonian fluid electrolyte composition after mechanical thixotropy compared to the loss factor before mechanical thixotropy can be optionally 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 60%, 65%, 70% or 75%.

[0086] Under the action of external forces such as needle puncture or extrusion, the non-Newtonian fluid electrolyte composition changes from a flowable state to a solid state. The phase change causes its loss factor to decrease. The decrease rate of the loss factor of the non-Newtonian fluid electrolyte composition exceeds 10%, that is, the storage modulus increases significantly, thereby effectively improving the safety and impact resistance of the battery in the event of accidents such as needle puncture.

[0087] In some embodiments, the non-Newtonian fluid electrolyte composition comprises at least one of an organic solvent and an ionic liquid, an electrolyte salt, and suspended particles.

[0088] As used herein, the term "organic solvent" refers to an organic compound containing carbon atoms, which has dielectric properties and can dissolve electrolyte salts.

[0089] As used herein, the term "ionic liquid" refers to a liquid composed of ions, which has no dielectric properties and can dissociate electrolyte salts.

[0090] Herein, the term "electrolyte salt" refers to a compound in which metal ions are combined with acid ions, and the electrolyte salt itself is capable of conducting electricity when dissolved in an aqueous solution or in a molten state.

[0091] As used herein, the term "suspended particles" refers to particles uniformly dispersed in a non-Newtonian electrolyte composition system, and the suspended particles include but are not limited to one or more of organic particles and inorganic particles.

[0092] In some embodiments, the non-Newtonian fluid electrolyte composition comprises an organic solvent, an electrolyte salt, and suspended particles.

[0093] In some embodiments, the non-Newtonian fluid electrolyte composition comprises an ionic liquid, an electrolyte salt, and suspended particles.

[0094] Non-Newtonian fluid electrolyte compositions comprising an electrolyte salt, an ionic liquid, and suspended particles, or comprising an electrolyte salt, an organic solvent, and suspended particles, exhibit excellent safety and impact resistance. Furthermore, these non-Newtonian fluid electrolyte compositions achieve minimal electrolyte ohmic resistance and interfacial resistance at low stacking pressures, simplifying the battery assembly process.

[0095] In some embodiments, the non-Newtonian fluid electrolyte composition further comprises a polymer.

[0096] In some embodiments, the non-Newtonian fluid electrolyte composition comprises an organic solvent, an electrolyte salt, a polymer, and suspended particles.

[0097] In some embodiments, the non-Newtonian fluid electrolyte composition comprises an ionic liquid, an electrolyte salt, a polymer, and suspended particles.

[0098] The introduction of polyethylene oxide into the non-Newtonian fluid electrolyte composition is beneficial to improving the cycle performance of the battery, reducing the battery expansion rate, reducing the gas production rate, and improving the safety of the battery.

[0099] In some embodiments, the electrolyte salt comprises a sodium salt, and the sodium salt comprises one or more of sodium chloride, sodium bromide, sodium nitrate, sodium perchlorate, sodium hexafluorophosphate, sodium acetate, sodium trifluoroacetate, sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide, and optionally comprises one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide.

[0100] In some embodiments, the sodium salt comprises sodium chloride. In some embodiments, the sodium salt comprises sodium bromide. In some embodiments, the sodium salt comprises sodium hexafluorophosphate. In some embodiments, the sodium salt comprises sodium tetrafluoroborate. In some embodiments, the sodium salt comprises sodium trifluoromethanesulfonate. In some embodiments, the sodium salt comprises sodium bis(fluorosulfonyl)imide. In some embodiments, the sodium salt comprises sodium bis(fluorosulfonyl)imide and sodium bis(trifluoromethylsulfonyl)imide. In some embodiments, the sodium salt comprises sodium tetrafluoroborate and sodium bis(fluorosulfonyl)imide.

[0101] The sodium salts described above are beneficial for improving the safety and impact resistance of non-Newtonian fluid electrolyte compositions, improving the cycle performance of batteries, reducing the gas production rate of batteries, and achieving the stacking pressure required to minimize the electrolyte ohmic resistance and interfacial resistance, thereby improving battery safety and the battery assembly process. The sodium salts may optionally include one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide, which further improves the cycle performance of the batteries.

[0102] In some embodiments, the organic solvent comprises one or more of an ether organic solvent, an ester organic solvent, and a sulfur-containing organic solvent, and comprises one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, fluoroethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, and dimethyl sulfoxide, and optionally comprises ethylene glycol dimethyl ether.

[0103] In some embodiments, the organic solvent comprises ethylene glycol dimethyl ether. In some embodiments, the organic solvent comprises diethylene glycol dimethyl ether. In some embodiments, the organic solvent comprises triethylene glycol dimethyl ether. In some embodiments, the organic solvent comprises tetraethylene glycol dimethyl ether. In some embodiments, the solvent comprises ethylene carbonate. In some embodiments, the organic solvent comprises ethylene glycol dimethyl ether and ethylene carbonate. In some embodiments, the organic solvent comprises ethylene glycol dimethyl ether and diethylene glycol dimethyl ether.

[0104] These organic solvents help improve the safety and impact resistance of non-Newtonian electrolyte compositions, reduce the stacking pressure required to minimize the electrolyte ohmic resistance and interfacial resistance, and improve the battery assembly process. The organic solvent optionally includes ethylene glycol dimethyl ether, which further improves the safety and impact resistance of the non-Newtonian electrolyte composition, significantly enhances the battery's cycling performance, significantly reduces the battery's gas production rate, and improves battery safety.

[0105] In some embodiments, the ionic liquid comprises one or more of 1-butyl-3-methylimidazole chloride, 1-alkyl-3-methylimidazole tetrafluoroborate, N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide, 5-azoniaspiro[4,4]nonane hexafluorophosphate, trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide, and tetrabutylphosphine hexafluorophosphate, and optionally comprises one or more of N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)amide and trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide.

[0106] In some embodiments, the ionic liquid comprises 1-butyl-3-methylimidazole chloride. In some embodiments, the ionic liquid comprises 1-alkyl-3-methylimidazole tetrafluoroboric acid. In some embodiments, the ionic liquid comprises N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide. In some embodiments, the ionic liquid comprises trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide. In some embodiments, the ionic liquid comprises tetrabutylphosphine hexafluorophosphate. In some embodiments, the ionic liquid comprises 1-butyl-3-methylimidazole chloride and tetrabutylphosphine hexafluorophosphate. In some embodiments, the ionic liquid comprises N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)amide and trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide.

[0107] The above-mentioned ionic liquid is beneficial for improving the safety and impact resistance of the non-Newtonian fluid electrolyte composition, reducing the stacking pressure of the battery when the electrolyte ohmic resistance and interface resistance are minimized, and improving the battery assembly process. Controlling the ionic liquid to optionally include one or more of N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide and trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide is beneficial for further improving the safety and impact resistance of the non-Newtonian fluid electrolyte composition, greatly improving the cycle performance of the battery, significantly reducing the battery's gas production rate and achieving the stacking pressure when the electrolyte ohmic resistance and interface resistance are minimized, improving the battery safety, and improving the battery assembly process.

[0108] In some embodiments, the polymer comprises polyethylene oxide, polyethylene glycol, polyvinyl pyrrolidone, polymethyl methacrylate, polyvinylidene fluoride, polyvinyl alcohol, polyacrylamide, and optionally comprises one or more of polyethylene oxide and polyethylene glycol.

[0109] In some embodiments, the polymer comprises polyethylene oxide. In some embodiments, the polymer comprises polyethylene glycol. In some embodiments, the polymer comprises polyvinyl pyrrolidone. In some embodiments, the polymer comprises polymethyl methacrylate. In some embodiments, the polymer comprises polyvinylidene fluoride. In some embodiments, the polymer comprises polyvinylidene fluoride and polyethylene oxide. In some embodiments, the polymer comprises polyethylene glycol and polyethylene oxide.

[0110] The aforementioned polymers are beneficial for improving the safety and impact resistance of non-Newtonian fluid electrolyte compositions, as well as reducing the battery's gas production rate and the stacking pressure required to minimize the electrolyte's ohmic resistance and interfacial resistance, thereby enhancing battery safety and improving the battery assembly process. The polymers can optionally include one or more of polyethylene oxide and polyethylene glycol, further improving the battery's cycling performance, significantly reducing the stacking pressure required to minimize the electrolyte's ohmic resistance and interfacial resistance, and improving the battery assembly process.

[0111] In some embodiments, the suspended particles include one or more of fumed silica, aluminum oxide, sodium oxide, lithium oxide, sodium fluoride, lithium fluoride, and polyurethane, and optionally include one or more of fumed silica, sodium oxide, and lithium oxide.

[0112] In some embodiments, the suspended particles comprise fumed silica. In some embodiments, the suspended particles comprise aluminum oxide. In some embodiments, the suspended particles comprise sodium oxide. In some embodiments, the suspended particles comprise sodium fluoride. In some embodiments, the suspended particles comprise polyurethane. The suspended particles comprise fumed silica and sodium oxide. The suspended particles comprise fumed silica and lithium fluoride. The suspended particles comprise sodium oxide and lithium fluoride. The suspended particles comprise fumed silica and polyurethane.

[0113] These suspended particles improve the safety and impact resistance of non-Newtonian electrolyte compositions, reduce the stacking pressure required to minimize the electrolyte ohmic resistance and interfacial resistance, and improve the battery assembly process. The suspended particles can optionally contain one or more of fumed silica, sodium oxide, and lithium oxide, further improving the battery's cycling performance, significantly reducing the battery's gas production rate, and enhancing battery safety.

[0114] In some embodiments, the electrolyte salt comprises one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide, the organic solvent comprises ethylene glycol dimethyl ether, the ionic liquid comprises one or more of N-alkyl-N-methylpiperidine bis(trifluoromethanesulfonyl)imide and trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide, the polymer comprises one or more of polyethylene oxide and polyethylene glycol, and the suspended particles comprise one or more of fumed silica, sodium oxide, and lithium oxide.

[0115] In some embodiments, the electrolyte salt comprises sodium trifluoromethanesulfonate, the organic solvent comprises ethylene glycol dimethyl ether, the polymer comprises polyethylene oxide, and the suspended particles comprise fumed silica. In some embodiments, the electrolyte salt comprises sodium bis(fluorosulfonyl)imide, the ionic liquid comprises N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide, the polymer comprises polyethylene oxide, and the suspended particles comprise fumed silica.

[0116] The selection of the above-mentioned electrolyte salt, organic solvent, ionic liquid, polymer and suspended particles is beneficial to improving the cycle performance of the battery.

[0117] In some embodiments, the electrolyte salt comprises one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide, the organic solvent comprises ethylene glycol dimethyl ether, and the suspended particles comprise one or more of fumed silica, sodium oxide, and lithium oxide.

[0118] In some embodiments, the electrolyte salt comprises sodium trifluoromethanesulfonate, the organic solvent comprises ethylene glycol dimethyl ether, and the suspended particles comprise fumed silica. In some embodiments, the electrolyte salt comprises sodium bis(fluorosulfonyl)imide, the organic solvent comprises ethylene glycol dimethyl ether, and the suspended particles comprise lithium oxide. In some embodiments, the electrolyte salt comprises sodium bis(trifluoromethylsulfonyl)imide, the organic solvent comprises ethylene glycol dimethyl ether, and the suspended particles comprise fumed silica.

[0119] The above-mentioned non-Newtonian fluid electrolyte composition comprising electrolyte salt, organic solvent and suspended particles is beneficial to improving the safety and impact resistance of the non-Newtonian fluid electrolyte composition, improving the cycle performance of the battery, and reducing the gas production rate of the battery and achieving the stacking pressure when the electrolyte ohmic resistance and interface resistance are minimized, thereby improving the safety of the battery and improving the battery assembly process.

[0120] In some embodiments, the electrolyte salt comprises one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide, the organic solvent comprises ethylene glycol dimethyl ether, the polymer comprises one or more of polyethylene oxide and polyethylene glycol, and the suspended particles comprise one or more of fumed silica, sodium oxide, and lithium oxide.

[0121] In some embodiments, the electrolyte salt comprises sodium trifluoromethanesulfonate, the organic solvent comprises ethylene glycol dimethyl ether, the polymer comprises polyethylene oxide, and the suspended particles comprise fumed silica. In some embodiments, the electrolyte salt comprises sodium bis(fluorosulfonyl)imide, the organic solvent comprises ethylene glycol dimethyl ether, the polymer comprises polyethylene glycol, and the suspended particles comprise lithium oxide. In some embodiments, the electrolyte salt comprises sodium bis(trifluoromethylsulfonyl)imide, the organic solvent comprises ethylene glycol dimethyl ether, the polymer comprises polyethylene oxide and polyethylene glycol, and the suspended particles comprise sodium oxide.

[0122] The above-mentioned non-Newtonian fluid electrolyte composition comprising electrolyte salt, organic solvent, polymer and suspended particles is beneficial to improving the safety and impact resistance of the non-Newtonian fluid electrolyte composition, improving the cycle performance of the battery, and reducing the gas production rate of the battery and achieving the stacking pressure when the electrolyte ohmic resistance and interface resistance are minimized, thereby improving the safety of the battery and improving the battery assembly process.

[0123] In some embodiments, the electrolyte salt comprises one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide, the ionic liquid comprises one or more of N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide and trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide, and the suspended particles comprise one or more of fumed silica, sodium oxide, and lithium oxide.

[0124] In some embodiments, the electrolyte salt comprises sodium trifluoromethanesulfonate, the ionic liquid comprises N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide, and the suspended particles comprise fumed silica. In some embodiments, the electrolyte salt comprises sodium bis(fluorosulfonyl)imide, the ionic liquid comprises N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide, and the suspended particles comprise sodium oxide. In some embodiments, the electrolyte salt comprises sodium bis(trifluoromethanesulfonyl)imide, the ionic liquid comprises N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide and trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide, and the suspended particles comprise lithium oxide.

[0125] The above-mentioned non-Newtonian fluid electrolyte composition comprising electrolyte salt, ionic liquid and suspended particles is beneficial to improving the safety and impact resistance of the non-Newtonian fluid electrolyte composition, reducing the stacking pressure of the battery when the electrolyte ohmic resistance and interface resistance are minimized, and improving the battery assembly process.

[0126] In some embodiments, the electrolyte salt comprises one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide; the ionic liquid comprises one or more of N-alkyl-N-methylpiperidine bis(trifluoromethanesulfonyl)imide and trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide; the polymer comprises one or more of polyethylene oxide and polyethylene glycol; and the suspended particles comprise one or more of fumed silica, sodium oxide, and lithium oxide.

[0127] In some embodiments, the electrolyte salt comprises sodium trifluoromethanesulfonate, the ionic liquid comprises N-alkyl-N-methylpiperidine bis(trifluoromethanesulfonyl)imide, the polymer comprises polyethylene oxide, and the suspended particles comprise fumed silica. In some embodiments, the electrolyte salt comprises sodium bis(fluorosulfonyl)imide, the ionic liquid comprises N-alkyl-N-methylpiperidine bis(trifluoromethanesulfonyl)imide, the polymer comprises polyethylene oxide and polyethylene glycol, and the suspended particles comprise lithium oxide. In some embodiments, the electrolyte salt comprises sodium bis(trifluoromethylsulfonyl)imide, the ionic liquid comprises N-alkyl-N-methylpiperidine bis(trifluoromethanesulfonyl)imide and trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide, the polymer comprises polyethylene glycol, and the suspended particles comprise fumed silica and lithium oxide.

[0128] The above-mentioned non-Newtonian fluid electrolyte composition comprising electrolyte salt, ionic liquid, polymer and suspended particles is beneficial to improving the safety and impact resistance of the non-Newtonian fluid electrolyte composition, reducing the stacking pressure of the battery when the electrolyte ohmic resistance and interface resistance are minimized, and improving the battery assembly process.

[0129] In some embodiments, based on the total mass of the non-Newtonian fluid electrolyte composition, the mass content of the electrolyte salt is 5% to 20%, the mass content of the organic solvent is 20% to 60%, the mass content of the ionic liquid is 20% to 60%, the mass content of the polymer is 0% to 40%, and the mass content of the suspended particles is greater than 0 and less than or equal to 20%.

[0130] In some embodiments, based on the total mass of the non-Newtonian fluid electrolyte composition, the mass content of the electrolyte salt may be 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16%, 18% or 20%, the mass content of the organic solvent may be 20%, 22%, 25%, 30%, 35%, 38%, 40%, 45%, 47%, 50%, 53%, 55%, 60%, 62% or 65%, and the mass content of the ionic liquid may be 20%, 22%, 25%, 30%, 35%, 38%, 40%, 45%, 47%, 50%, 53%, 55%, 60%, 62% or 65%. The weight content of the polymer can be selected from the group consisting of 0%, 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16%, 18%, 20%, 22%, 25%, 28%, 30%, 35%, 38% and 40%, and the weight content of the suspended particles can be selected from the group consisting of 1%, 2%, 4%, 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16%, 18% and 20%.

[0131] Controlling the appropriate mass content of electrolyte salts, organic solvents, ionic liquids, polymers, and suspended particles is beneficial for improving the safety and impact resistance of non-Newtonian fluid electrolyte compositions, enhancing battery cycle performance, reducing battery gas production rates, and achieving the stacking pressure required to minimize electrolyte ohmic resistance and interfacial resistance, thereby improving battery safety and assembly processes. This enhances interfacial stability while ensuring the diffusion of metal ions.

[0132] In some embodiments, the non-Newtonian fluid electrolyte composition has a compressive strength of 35 kN to 200 kN.

[0133] In this article, the extrusion strength at zero open-circuit voltage is primarily used to characterize the pressure a non-Newtonian electrolyte composition withstands when the battery is short-circuited. This reflects the impact resistance of the non-Newtonian electrolyte composition and can be tested using any known method. For example, a semi-cylindrical extrusion plate with a radius of 75 mm is positioned perpendicular to the battery electrode at a speed of 60 mm / min. The changes in the battery's open-circuit voltage and the pressure applied by the extrusion plate are observed, and the pressure applied when the open-circuit voltage is zero is recorded.

[0134] The non-Newtonian fluid electrolyte composition has suitable extrusion strength, which is beneficial to improving its impact resistance and enhancing the safety and reliability of the battery.

[0135] [Positive electrode]

[0136] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer formed on at least a portion of the surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, which may include at least one of a layered transition metal oxide, a polyanionic compound, and a Prussian blue compound.

[0137] The transition metal in the layered transition metal oxide can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. Optionally, the layered transition metal oxide is, for example, NaxMO2, wherein M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr, and Cu, and 0<x≤1.

[0138] Polyanionic compounds can be metal ions, transition metal ions and tetrahedral (YO4) n- A class of compounds with anionic units. The metal ion can be selected from sodium ion, lithium ion, potassium ion, and zinc ion; the transition metal can be selected from at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce; Y can be selected from at least one of P, S, and Si; n represents (YO4) n- valence.

[0139] Prussian blue compounds can be compounds containing sodium ions, transition metal ions, and cyanide ions (CN-). The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. Prussian blue compounds are, for example, Na a Me b Me' c (CN)6, wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co and Zn, 0<a≤2, 0<b<1, 0<c<1.

[0140] In some embodiments, the positive electrode sheet includes a positive electrode active material, the positive electrode active material includes at least one of a layered transition metal oxide, a polyanion compound, and a Prussian blue compound, including NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2、Na(Cu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 )O2、Na 2 / 3 Ni 1 / 6 Mn 2 / 3 Cu 1 / 9 Mg 1 / 18 O2, Na4Fe3(PO4)2P2O7, NaFePO4, Na3V2(PO4)3, Na1.9 One or more of CoFe(CN)6, Na2NiFe(CN)6, and NaMnFe(CN)6.

[0141] The above-mentioned positive electrode active materials can all make the battery have excellent cycle performance and safety.

[0142] In some embodiments, the surface of the positive electrode active material has a coating layer, which includes one or more of carbon material, ZrO2, TiO2, polyaniline, polypyrrole, poly(3,4-ethylenedioxythiophene), aluminum oxide, zinc oxide, titanium oxide, zirconium oxide, magnesium oxide, silicon oxide, lanthanum oxide, sodium fluoride, lithium fluoride and aluminum fluoride, and the carbon material includes one or more of amorphous carbon, graphite and graphene.

[0143] As used herein, the term "amorphous carbon" refers to a carbon material with a low degree of graphitization and crystallization, which is approximately amorphous and has no specific shape or periodic structure. Examples of amorphous carbon include, but are not limited to, carbon black, charcoal, or coke.

[0144] As used herein, the term "graphite" refers to an allotrope of carbon, including natural graphite and artificial graphite.

[0145] As used herein, the term "graphene" refers to a carbon material in which carbon atoms connected by sp2 hybridization are closely packed into a single-layer two-dimensional honeycomb lattice structure. By way of example, graphene includes but is not limited to single-layer graphene or multi-layer graphene.

[0146] As used herein, the term "single-layer graphene" refers to a single-layer sheet structure composed of carbon atoms densely arranged in a periodic hexagonal honeycomb structure. For example, the thickness of a single-layer graphene is only 0.3 nm to 0.4 nm.

[0147] In this article, the term "multilayer graphene" refers to a stack of 2 to 10 single-layer graphene layers with a total thickness of less than 100 nm.

[0148] The surface of the positive electrode active material has a coating layer, which is more conducive to improving the cycle performance, greatly reducing the gas production rate of the battery, and improving the safety of the battery.

[0149] The positive electrode active material layer may further include a conductive agent to improve the conductivity of the positive electrode. The conductive agent may be selected from one or more of Super P, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene, and carbon nanofibers.

[0150] The positive electrode active material layer may further include a binder to firmly bond the positive electrode active material and optional conductive agent to the positive electrode current collector. The binder may be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), polyvinyl alcohol (PVA), ethylene-vinyl acetate copolymer (EVA), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), sodium alginate (SA), polymethacrylic acid (PMA), and carboxymethyl chitosan (CMCS).

[0151] The positive electrode current collector can be a conductive carbon sheet, metal foil, carbon-coated metal foil, porous metal plate, or a composite current collector. The conductive carbon material of the conductive carbon sheet can be selected from one or more of Super P, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene, and carbon nanofibers. The metal material of the metal foil, carbon-coated metal foil, and porous metal plate can each be independently selected from at least one of copper, aluminum, nickel, and stainless steel. The composite current collector can be a composite of metal foil and a polymer-based film.

[0152] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0153] [Negative electrode]

[0154] The negative electrode plate may only include a negative electrode current collector without including a negative electrode active material. The negative electrode plate may also be formed by pre-depositing a metal phase on the negative electrode current collector.

[0155] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil or copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0156] In some embodiments, the negative electrode plate includes a negative electrode current collector and a primer layer disposed on at least one surface of the negative electrode current collector, wherein the primer layer includes one or more of carbon nanotubes, graphite, graphene, silver composite carbon nanoparticles, and tin composite carbon nanoparticles.

[0157] In some embodiments, the surface density of the primer layer is 2-50 g / m 2 .

[0158] In some embodiments, the primer layer has a thickness of 1-100 μm.

[0159] [Isolation film]

[0160] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.

[0161] In some embodiments, the material of the separator can be selected from at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester, and natural fibers. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0162] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.

[0163] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.

[0164] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0165] [Secondary battery]

[0166] A secondary battery includes a positive electrode and a non-Newtonian fluid electrolyte composition in some embodiments.

[0167] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG2 shows a secondary battery 5 having a square structure as an example.

[0168] In some embodiments, the secondary battery further includes a negative electrode sheet and a separator.

[0169] In some embodiments, the secondary battery includes at least one of a lithium battery and a sodium battery.

[0170] In some embodiments, the secondary battery includes at least one of a potassium battery, a magnesium battery, and a zinc battery.

[0171] In some embodiments, the secondary battery is a negative electrode-less sodium battery.

[0172] There is no pre-deposition of negative electrode active materials in the negative electrode-free sodium battery, which only contains a negative electrode current collector. During the first charge, sodium ions obtain electrons on the cathode side and deposit metallic sodium on the surface of the current collector to form a sodium metal phase. During discharge, metallic sodium can be converted into sodium ions and return to the positive electrode to achieve cyclic charge and discharge. Compared with sodium ion secondary batteries and sodium metal batteries, negative electrode-free sodium batteries can achieve higher energy density because they are not restricted by negative electrode materials. There is not enough sodium metal in the negative electrode-free sodium battery as a negative electrode material to provide enough sodium elements to the battery. Therefore, the application of non-Newtonian fluid electrolyte compositions in negative electrode-free sodium batteries can more effectively improve the cycle performance and safety performance of secondary batteries at room temperature / high temperature.

[0173] In some embodiments, the CB value of the negative electrode-free sodium battery is less than or equal to 0.1.

[0174] The CB value is the capacity per unit area of ​​the negative electrode in a secondary battery divided by the capacity per unit area of ​​the positive electrode. Since a battery without a negative electrode contains no negative active material, the capacity per unit area of ​​the negative electrode is relatively small, and the CB value of a secondary battery is less than or equal to 0.1.

[0175] In some embodiments, referring to Figure 3, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The non-Newtonian fluid electrolyte composition is impregnated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0176] [Battery Module]

[0177] In some embodiments, secondary batteries can be assembled into a battery module. The number of secondary batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0178] Figure 4 shows an example battery module 4. Referring to Figure 4 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.

[0179] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0180] [Battery Pack]

[0181] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.

[0182] Figures 5 and 6 illustrate an example battery pack 1. Referring to Figures 5 and 6 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be positioned over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0183] [Electrical devices]

[0184] In one embodiment of the present application, an electric device is provided, comprising at least one of a secondary battery according to any embodiment, a battery module according to any embodiment, or a battery pack according to any embodiment.

[0185] The electrical device includes at least one of the secondary battery, battery module, or battery pack provided in this application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.

[0186] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0187] Figure 7 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.

[0188] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.

[0189] Example

[0190] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.

[0191] 1. Preparation method

[0192] Example 1

[0193] 1) Preparation of non-Newtonian fluid electrolyte composition

[0194] In a dry argon atmosphere, polyethylene oxide (PEO, weight-average molecular weight of 600,000), fumed silica, sodium bis(fluorosulfonyl)imide (NaFSI) and N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide ionic liquid were mixed in a mass ratio of 5:2:3:10 and stirred evenly to completely dissolve NaFSI to obtain a non-Newtonian fluid electrolyte composition.

[0195] 2) Preparation of positive electrode sheet

[0196] Na4Fe3(PO4)2P2O7 (NFPP) material, conductive agent carbon black, polyvinylidene fluoride binder and N-methylpyrrolidone (NMP) are stirred and mixed in a weight ratio of 8:1:1 to obtain a positive electrode slurry; the positive electrode slurry is then evenly coated on the surface of the positive electrode current collector aluminum foil, and after drying, cold pressing and slitting, the positive electrode sheet is obtained.

[0197] 3) Preparation of negative electrode sheet

[0198] Carbon nanotubes and hydroxymethyl cellulose (CMC) were added to deionized water in a mass ratio of 1:0.4 and stirred into a uniform slurry. The slurry was coated on the negative electrode current collector copper foil, dried and cut to obtain a negative electrode sheet without a negative electrode structure. The surface density of the base coating was 10 g / m 2 , wherein the thickness of the primer layer is 5 μm.

[0199] 4) Isolation film

[0200] Polypropylene film is used as the isolation film.

[0201] 5) Preparation of batteries

[0202] A non-Newtonian fluid electrolyte composition is cast onto both sides of a separator. The positive electrode sheet, the separator coated with the non-Newtonian fluid electrolyte composition, and the negative electrode sheet are then stacked in sequence, with the separator positioned between the positive and negative electrodes to provide isolation. The process is then wound to obtain a bare cell. The tabs are welded to the bare cell, which is then encased in an aluminum shell and baked at 80°C to remove water, yielding an uncharged battery. The uncharged battery then undergoes a series of steps, including resting, hot and cold pressing, formation, shaping, and capacity testing, to obtain the negative-electrode-free sodium battery product of Example 1.

[0203] Examples 2 to 4

[0204] The preparation methods of the batteries of Examples 2 to 4 are similar to that of the battery of Example 1, but the type of sodium salt is adjusted. The specific parameters are shown in Table 1.

[0205] Examples 5-6

[0206] The preparation methods of the batteries of Examples 5 and 6 are similar to those of the battery of Example 1, but the types of ionic liquids are adjusted. The specific parameters are shown in Table 1.

[0207] Examples 7-8

[0208] The batteries of Examples 7-8 were prepared in a similar manner to that of Example 1, except that the type of polymer was adjusted. The specific parameters are shown in Table 1.

[0209] Example 9

[0210] The preparation method of the battery of Example 9 is similar to that of the battery of Example 1, but the preparation method of the non-Newtonian fluid electrolyte composition is adjusted. The preparation method is as follows:

[0211] In a dry argon atmosphere, polyethylene oxide (PEO, weight-average molecular weight of 600,000), polyethylene glycol (PEG, weight-average molecular weight of 10,000), sodium bis(fluorosulfonyl)imide (NaFSI) and N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide ionic liquid were mixed in a mass ratio of 5:2:3:10 and stirred evenly to completely dissolve NaFSI to obtain a non-Newtonian fluid electrolyte composition.

[0212] Examples 10 to 13

[0213] The batteries of Examples 10 to 13 were prepared in a similar manner to the battery of Example 1, except that the types of suspended particles were adjusted. The specific parameters are shown in Table 1.

[0214] Example 14

[0215] The preparation method of the battery of Example 14 is similar to that of the battery of Example 1, but the mass contents of the sodium salt, ionic liquid, polymer and suspended particles are adjusted. The specific parameters are shown in Table 1.

[0216] Example 15

[0217] The preparation method of the battery of Example 15 is similar to that of the battery of Example 1, but the preparation method of the non-Newtonian fluid electrolyte composition is adjusted, and the preparation method is as follows:

[0218] In a dry argon atmosphere, fumed silica, sodium bis(fluorosulfonyl)imide (NaFSI) and N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide ionic liquid were mixed in a mass ratio of 1:1:3, stirred evenly to completely dissolve NaFSI, and then cooled to room temperature to obtain a non-Newtonian fluid electrolyte composition.

[0219] Examples 16-17

[0220] The preparation methods of the batteries of Examples 16 to 17 are similar to those of the battery of Example 15, but the types of ionic liquids and suspended particles are adjusted respectively. The specific parameters are shown in Table 1.

[0221] Example 18

[0222] The preparation method of the battery of Example 18 is similar to that of the battery of Example 1, but the preparation method of the non-Newtonian fluid electrolyte composition is adjusted. The preparation method is as follows:

[0223] In a dry argon atmosphere, polyethylene oxide (PEO, weight-average molecular weight of 600,000), fumed silica, sodium bis(fluorosulfonyl)imide (NaFSI) and an organic solvent, ethylene glycol dimethyl ether (DME), were mixed in a mass ratio of 5:2:3:10 and stirred evenly to completely dissolve the NaFSI to obtain a non-Newtonian fluid electrolyte composition.

[0224] Examples 19-20

[0225] The batteries of Examples 19 to 20 were prepared in a similar manner to that of Example 18, except that the type of organic solvent was adjusted. The specific parameters are shown in Table 1.

[0226] Example 21

[0227] The preparation method of the battery of Example 21 is similar to that of the battery of Example 18, but the mass contents of the sodium salt, organic solvent, polymer and suspended particles are adjusted. The specific parameters are shown in Table 1.

[0228] Example 22

[0229] The preparation method of the battery of Example 22 is similar to that of the battery of Example 18, but the preparation method of the non-Newtonian fluid electrolyte composition is adjusted. The preparation method is as follows:

[0230] In a dry argon atmosphere, fumed silica, sodium bis(fluorosulfonyl)imide (NaFSI) and an organic solvent, ethylene glycol dimethyl ether (DME), were mixed in a mass ratio of 1:1:3, stirred evenly to completely dissolve the NaFSI, and then cooled to room temperature to obtain a non-Newtonian fluid electrolyte composition.

[0231] Examples 23-24

[0232] The preparation methods of the batteries of Examples 23 to 24 are similar to those of the battery of Example 22, except that the types of organic solvents and suspended particles are adjusted. The specific parameters are shown in Table 1.

[0233] Examples 25-26

[0234] The preparation methods of the batteries of Examples 25 to 26 are similar to those of Example 1, but the types of positive electrode active materials are adjusted. The specific parameters are shown in Table 1. Among them, the thickness of the ZrO2 coating layer in Example 26 is 30 nm.

[0235] Examples 27 to 33

[0236] The preparation methods of the batteries of Examples 27 to 33 are similar to those of the battery of Example 1, but the mass contents of the sodium salt, ionic liquid, polymer, and suspended particles are adjusted. The specific parameters are shown in Table 1.

[0237] Comparative Example 1

[0238] The battery of Comparative Example 1 is prepared in a similar manner to that of Example 1, except that the preparation method of the electrolyte is adjusted. The preparation method is as follows:

[0239] In a dry argon atmosphere, polyethylene oxide (PEO, weight-average molecular weight of 600,000), sodium bis(fluorosulfonyl)imide (NaFSI) and organic solvent ethylene glycol dimethyl ether (DME) were mixed in a mass ratio of 7:3:10, stirred evenly to completely dissolve NaFSI, and then cooled to room temperature to obtain a quasi-solid electrolyte.

[0240] Comparative Example 2

[0241] The preparation method of the battery of Comparative Example 2 is similar to that of the battery of Comparative Example 1, but the mass contents of the sodium salt, the organic solvent and the polymer are adjusted. The specific parameters are shown in Table 1.

[0242] Comparative Examples 3 to 5

[0243] The batteries of Comparative Examples 3 to 5 were prepared in a similar manner to the battery of Comparative Example 1, except that the type of sodium salt was adjusted. The specific parameters are shown in Table 1.

[0244] Comparative Example 6

[0245] The preparation method of the battery of Example 6 is similar to that of the battery of Comparative Example 1, but the type of solvent is adjusted. The specific parameters are shown in Table 1.

[0246] Comparative Examples 7 to 9

[0247] The preparation methods of the batteries of Examples 7 to 9 are similar to those of the battery of Comparative Example 1, but they use liquid electrolytes and adjust the types of positive electrode materials, as shown in Table 1. Specifically, the thickness of the ZrO2 coating layer in Comparative Example 9 is 30 nm.

[0248] 2. Performance Testing

[0249] 1. Performance test of non-Newtonian fluid electrolyte composition

[0250] 1) Viscosity test

[0251] The non-Newtonian electrolyte composition was subjected to rotational testing using a Brookfield Dveslvtjo rotational viscometer. The viscosity values ​​were recorded after 10 seconds and 10 minutes, respectively. The test conditions were: 25°C, 12 rpm, a #64 spindle for viscosities of 2000 mPa·s or higher, and a #62 spindle for viscosities below 2000 mPa·s. Three replicate measurements were performed, and the average value was calculated.

[0252] 2) Loss factor test

[0253] The test instrument is a Haake rheometer; the non-Newtonian fluid electrolyte composition sample is cut into a disc with a diameter of 20 mm and a thickness of 1 mm; the test temperature is 25°C; the strain sweep range is 0.1% to 1000%, and the fixed frequency is 1 Hz. The storage modulus (G') and loss modulus (G") are obtained, and the loss factor (tan δ) is calculated as tan δ = G" / G'

[0254] 3) Acupuncture strength test

[0255] Prepare and assemble single-layer laminated or soft-pack batteries based on a non-Newtonian fluid electrolyte combination, fix them under a test fixture, use a high-speed rail tensile tester and a puncture fixture, use a 1mm diameter needle on the puncture tester, and puncture at a speed of 6mm / min. When the depth reaches 2mm, stop and let the battery stand to observe the change in open circuit voltage, and record the time required for the open circuit voltage to drop to 2mV.

[0256] 4) Extrusion strength test

[0257] Place a semi-cylindrical extrusion plate with a radius of 75 mm perpendicular to the direction of the battery electrode at an extrusion speed of 60 mm / min. Observe the changes in the battery open circuit voltage and the pressure applied by the extrusion plate, and record the pressure applied by the extrusion plate when the open circuit voltage is zero.

[0258] 2. Battery performance test

[0259] 1) Coulomb efficiency test

[0260] The coulomb test process is as follows: at 25°C, the prepared battery is charged at a constant current of 0.1C to 3.7V (sodium iron pyrophosphate positive electrode) or 4.0V (layered oxide positive electrode), then charged at a constant voltage of 3.7V until the current drops to 0.01C to obtain the initial charge capacity (Cc1), and then discharged at a constant current of 0.1C to 2.5V to obtain the initial discharge capacity (Cd1). n charge and discharge cycles are performed, and the number of cycles n at which the capacity decays to 80% is recorded. The average coulomb efficiency of the battery is calculated according to the following formula:

[0261] Coulomb efficiency of each cycle = discharge capacity of the cycle (Cd1) / charge capacity of the cycle (Cc1) × 100%,

[0262] The average value of the coulombic efficiency from the second circle to the nth weight is taken as the average coulombic efficiency of the battery.

[0263] The testing procedures of the comparative example and other embodiments are the same as above.

[0264] 2) Cycle test to maintain capacity at 80%

[0265] The test process for the number of cycles to retain the capacity to 80% is as follows: at 25°C, the prepared battery is charged at a constant current of 1C to 3.7V (sodium iron pyrophosphate positive electrode) or 4.0V (layered oxide positive electrode), then charged at a constant voltage of 3.7V until the current drops to 0.1C, and then discharged at 1C to 2.5V. The obtained capacity is recorded as the initial capacity (C0). Repeat the above steps for the same battery mentioned above, and record the discharge capacity (Cn) of the battery after the nth cycle at the same time. The battery capacity retention rate after each cycle is Pn = Cn / C0×100%, and the number of cycles of the battery is recorded when Pn drops to 80%. The test process of the comparative example and other embodiments is the same as above.

[0266] 3) Cyclic gas production performance test

[0267] The cyclic gas generation performance test procedure is as follows: at 25°C, the first charge and discharge were performed. Constant current and constant voltage charging was performed at a charge current of 1C until the upper limit voltage reached approximately 3.7V (sodium iron pyrophosphate positive electrode) or 4.0V (layered oxide positive electrode). Then, constant current discharge was performed at a discharge current of 1C until the final voltage reached approximately 2.5V. The battery thickness D1 at this time was recorded. Then, n charge and discharge cycles were performed. The number of cycles n at which the capacity decayed to 80% and the thickness Dn after the nth cycle were recorded. The gas generation performance was calculated as follows: Expansion rate to 80% capacity retention = (Dn-D1) / D1×100%. The testing procedures for the comparative example and other examples were the same as above.

[0268] 4) Stack stress test

[0269] The stacking pressure test process is as follows: A certain pressure F is applied to the battery surface using a battery fixture. This pressure can be controlled by adjusting the pressure applied by the punch and the screws in the battery fixture. The specific value is output by the battery's built-in pressure sensor. Using an AC impedance test in an electrochemical workstation, the impedance R, representing the sum of the electrolyte ohmic resistance and the interface resistance, is obtained. With pressure as the horizontal axis and impedance as the vertical axis, an impedance-pressure curve is generated, and the F value at which the impedance R is minimum is recorded.

[0270] 3. Analysis of test results of various embodiments and comparative examples

[0271] Batteries of various examples and comparative examples were prepared according to the above methods, and various performance parameters were measured. The results are shown in Tables 1 to 3 below.

[0272] Table 1

[0273]

[0274]

[0275]

[0276] Table 2

[0277]

[0278]

[0279] Table 3

[0280]

[0281]

[0282] According to the above results, the viscosity of the non-Newtonian fluid electrolyte compositions of Examples 1 to 33 changes with shear time under the action of shear force, wherein the sodium salt in the non-Newtonian fluid electrolyte composition is selected from sodium chloride, sodium hexafluorophosphate, sodium trifluoromethanesulfonate, or sodium bis(fluorosulfonyl)imide; the ionic liquid in the non-Newtonian fluid electrolyte composition is selected from N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide, trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide, or 1-alkyl-3-methylimidazole tetrafluoroborate; the organic solvent in the non-Newtonian fluid electrolyte composition is selected from ethylene glycol dimethyl ether, ethylene carbonate, or dimethyl sulfoxide; the polymer in the non-Newtonian fluid electrolyte composition is selected from one or two of polyethylene oxide, polyethylene glycol, and polyvinyl pyrrolidone; and the suspended particles in the non-Newtonian fluid electrolyte composition are selected from fumed silica, sodium oxide, lithium oxide, polyurethane, or sodium fluoride.

[0283] From the comparison of Examples 1 to 33 and Comparative Examples 1 to 6, it can be seen that compared with traditional electrolytes, the non-Newtonian fluid electrolyte composition does not satisfy Newton's viscosity law. After mechanical thixotropy, the loss factor of the non-Newtonian fluid electrolyte combination decreases by more than 10% (loss factor decrease rate = (loss factor before mechanical thixotropy - loss factor after mechanical thixotropy) / loss factor before mechanical thixotropy × 100%), which is beneficial to improving the extrusion strength when the open circuit voltage reaches zero, and reducing the stacking pressure when the electrolyte ohmic resistance and interface resistance are minimized, significantly improving the impact resistance of the battery, and improving the battery assembly process.

[0284] From the comparison between Example 14 and Example 15, and Example 21 and Example 22, it can be seen that the introduction of polyethylene oxide into the non-Newtonian fluid electrolyte composition is beneficial to increasing the number of cycles when the capacity retention rate of the battery reaches 80%, and reducing the expansion rate when the capacity retention rate reaches 80%.

[0285] From the comparison of Examples 1 and 18 with Comparative Example 1, Examples 14-15, 21-22 with Comparative Example 2, Example 2 with Comparative Example 3, Example 3 with Comparative Example 4, Example 4 with Comparative Example 5, and Example 19 with Comparative Example 6, it can be seen that the sodium salt in the non-Newtonian fluid electrolyte composition is selected from sodium chloride, sodium hexafluorophosphate, sodium trifluoromethanesulfonate, or sodium bis(fluorosulfonyl)imide, which is beneficial for increasing the time it takes for the open circuit voltage of the non-Newtonian fluid electrolyte composition to drop to 2 mV after acupuncture and the compressive strength when the open circuit voltage reaches zero, as well as increasing the number of cycles when the battery capacity retention rate reaches 80%, reducing the expansion rate when the battery capacity retention rate reaches 80%, and achieving the stacking pressure at which the electrolyte ohmic resistance and interfacial resistance are minimized. From the comparison of Examples 1 and 3 with Examples 2 and 4, it can be seen that controlling the sodium salt to be selected from sodium trifluoromethanesulfonate or sodium bis(fluorosulfonyl)imide is beneficial for increasing the rate of decrease in the loss factor of the non-Newtonian fluid electrolyte composition after mechanical thixotropy, further improving the average coulombic efficiency of the battery, and significantly increasing the number of cycles when the capacity retention rate reaches 80%.

[0286] From the comparison of Examples 1, 5 to 6 with Comparative Example 1, and Examples 14 to 16 with Comparative Example 2, it can be seen that the ionic liquid in the non-Newtonian fluid electrolyte composition is selected from N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide, trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide or 1-alkyl-3-methylimidazole tetrafluoroborate, which is beneficial to increasing the time it takes for the open circuit voltage of the non-Newtonian fluid electrolyte composition to drop to 2 mV after acupuncture and the extrusion strength when the open circuit voltage reaches zero, reducing the stacking pressure at which the electrolyte ohmic resistance and interface resistance are minimized, and improving the battery assembly process. From the comparison of Examples 1 and 5 with Example 6, and Example 15 with Example 16, it can be seen that controlling the ionic liquid to be selected from N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide or trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide is beneficial to further improve the time for the open circuit voltage of the non-Newtonian fluid electrolyte composition to drop to 2 mV after acupuncture and the extrusion strength when the open circuit voltage reaches zero, and to a greater extent improve the average coulombic efficiency of the battery and the number of cycles when the capacity retention rate reaches 80%, and significantly reduce the expansion rate of the battery when the capacity retention rate reaches 80% and the stacking pressure at which the electrolyte ohmic resistance and interface resistance are minimized.

[0287] Comparison of Examples 1, 7-9 with Comparative Example 1 shows that the polymer in the non-Newtonian fluid electrolyte composition is selected from one or two of polyethylene oxide, polyethylene glycol, and polyvinyl pyrrolidone, which is beneficial for increasing the time it takes for the open circuit voltage of the non-Newtonian fluid electrolyte composition to drop to 2 mV after acupuncture and the compressive strength when the open circuit voltage reaches zero, as well as reducing the expansion rate when the battery capacity retention rate reaches 80% and the stacking pressure at which the electrolyte ohmic resistance and interface resistance are minimized. Comparison of Examples 1, 7, and 9 with Example 8 shows that controlling the polymer to be selected from one or two of polyethylene oxide and polyethylene glycol is beneficial for further improving the average coulombic efficiency of the battery and the number of cycles when the capacity retention rate reaches 80%, and significantly reducing the stacking pressure at which the electrolyte ohmic resistance and interface resistance are minimized.

[0288] Comparisons of Examples 1, 10-13 with Comparative Example 1, and Examples 14-15, 17, 21-22, and 24 with Comparative Example 2 show that the suspended particles in the non-Newtonian fluid electrolyte composition are selected from fumed silica, sodium oxide, lithium oxide, polyurethane, or sodium fluoride, which helps increase the time it takes for the open-circuit voltage of the non-Newtonian fluid electrolyte composition to drop to 2 mV after acupuncture, the compressive strength when the open-circuit voltage reaches zero, and reduce the stacking pressure at which the electrolyte ohmic resistance and interfacial resistance are minimized. Comparisons of Examples 1, 10-11 with Examples 12-13 show that controlling the suspended particles to be selected from fumed silica, sodium oxide, or lithium oxide further improves the battery's average coulombic efficiency and the number of cycles required for a capacity retention rate of 80%, and significantly reduces the battery's expansion rate at a capacity retention rate of 80%.

[0289] Comparisons of Examples 18 and 20 with Comparative Example 1, Examples 21-22 with Comparative Example 2, and Examples 19 and 23 with Comparative Example 6 show that the organic solvent in the non-Newtonian fluid electrolyte composition is selected from ethylene glycol dimethyl ether, ethylene carbonate, or dimethyl sulfoxide, which is beneficial for increasing the time it takes for the open circuit voltage of the non-Newtonian fluid electrolyte composition to drop to 2 mV after acupuncture and the squeezing strength when the open circuit voltage reaches zero, as well as reducing the stacking pressure at which the electrolyte ohmic resistance and interfacial resistance are minimized. Comparisons of Examples 18 with Examples 19-20, and Example 22 with Example 23 show that controlling the organic solvent to be selected from ethylene glycol dimethyl ether is beneficial for further increasing the time it takes for the open circuit voltage of the non-Newtonian fluid electrolyte composition to drop to 2 mV after acupuncture and the squeezing strength when the open circuit voltage reaches zero, further improving the average coulombic efficiency of the battery and the number of cycles at which the capacity retention rate reaches 80%, and significantly reducing the expansion rate of the battery at which the capacity retention rate reaches 80%.

[0290] From the comparison of Examples 1 and 3 with Examples 2 and 4, Examples 1 and 5 with Example 6, Example 15 with Example 16, Examples 1 and 8 to 9 with Example 7, Examples 1 and 10 to 11 with Examples 12 to 13, Example 18 with Examples 19 to 20, and Example 22 with Example 23, it can be seen that controlling the sodium salt to be selected from sodium trifluoromethanesulfonate or sodium bis(fluorosulfonyl)imide, the ionic liquid to be selected from N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide or trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide, the polymer to be selected from one or two of polyethylene oxide and polyethylene glycol, the suspended particles to be selected from fumed silica, sodium oxide or lithium oxide, and the organic solvent to be selected from ethylene glycol dimethyl ether are beneficial to further improve the average coulombic efficiency and significantly increase the number of cycles when the capacity retention rate reaches 80%.

[0291] From the comparison of Examples 1, 3, 5, 7, 8 to 11 with Comparative Example 1, and Example 14 with Comparative Example 2, it can be seen that controlling the sodium salt to be selected from sodium trifluoromethanesulfonate or sodium bis(fluorosulfonyl)imide, the ionic liquid to be selected from N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide or trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide, the polymer to be selected from one or two of polyethylene oxide and polyethylene glycol, and the suspended particles to be selected from fumed silica, sodium oxide or lithium oxide, are beneficial to increasing the time for the open circuit voltage of the non-Newtonian fluid electrolyte composition to drop to 2 mV after acupuncture and the extrusion strength when the open circuit voltage reaches zero, as well as reducing the stacking pressure when the electrolyte ohmic resistance and interface resistance are minimized.

[0292] From the comparison of Examples 1 and 3 with Examples 2 and 4, Examples 1 and 5 with Example 6, Examples 1 and 8 to 9 with Example 7, and Examples 1 and 10 to 11 with Examples 12 to 13, it can be seen that controlling the sodium salt to be selected from sodium trifluoromethanesulfonate or sodium bis(fluorosulfonyl)imide, the ionic liquid to be selected from N-alkyl-N-methylpiperidine bis(trifluoromethanesulfonyl)imide or trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide, the polymer to be selected from one or two of polyethylene oxide and polyethylene glycol, and the suspended particles to be selected from fumed silica, sodium oxide or lithium oxide, is conducive to further improving the average coulombic efficiency and the number of cycles when the capacity retention rate reaches 80%.

[0293] From the comparison of Examples 15 to 17 with Comparative Example 1, it can be seen that controlling the sodium salt to be selected from sodium bis(fluorosulfonyl)imide, the ionic liquid to be selected from N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide or trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide, and the suspended particles to be selected from fumed silica or sodium oxide are beneficial to increasing the time for the open circuit voltage of the non-Newtonian fluid electrolyte composition to drop to 2 mV after acupuncture and the extrusion strength when the open circuit voltage reaches zero, as well as reducing the stacking pressure when the electrolyte ohmic resistance and the interface resistance are minimized.

[0294] From the comparison between Example 18 and Comparative Example 1, and Example 21 and Comparative Example 2, it can be seen that controlling the sodium salt to be selected from sodium bis(fluorosulfonyl)imide, the organic solvent to be selected from ethylene glycol dimethyl ether, the polymer to be selected from polyethylene oxide, and the suspended particles to be selected from gas-phase silica, is beneficial to increasing the time for the open circuit voltage of the non-Newtonian fluid electrolyte composition to drop to 2 mV after acupuncture and the extrusion strength when the open circuit voltage reaches zero, as well as increasing the average coulombic efficiency of the battery and the number of cycles when the capacity retention rate reaches 80%, reducing the expansion rate of the battery when the capacity retention rate reaches 80%, and achieving the stacking pressure when the electrolyte ohmic resistance and interface resistance are minimized.

[0295] From the comparison between Example 18 and Examples 19 to 20, it can be seen that controlling the sodium salt to be selected from sodium bis(fluorosulfonyl)imide, the organic solvent to be selected from ethylene glycol dimethyl ether, the polymer to be selected from polyethylene oxide, and the suspended particles to be selected from fumed silica is beneficial to increasing the time for the open circuit voltage of the non-Newtonian fluid electrolyte composition to drop to 2 mV after acupuncture and the extrusion strength when the open circuit voltage reaches zero, thereby greatly improving the average coulombic efficiency of the battery and the number of cycles when the capacity retention rate reaches 80%, and significantly reducing the expansion rate of the battery when the capacity retention rate reaches 80%.

[0296] From the comparison of Examples 22 and 24 with Comparative Example 2, it can be seen that controlling the sodium salt to be selected from sodium bis(fluorosulfonyl)imide, the organic solvent to be selected from ethylene glycol dimethyl ether, and the suspended particles to be selected from fumed silica or sodium oxide is beneficial to increasing the time for the open circuit voltage of the non-Newtonian fluid electrolyte composition to drop to 2 mV after acupuncture and the extrusion strength when the open circuit voltage reaches zero, as well as increasing the number of cycles when the battery capacity retention rate reaches 80%, reducing the expansion rate when the battery capacity retention rate reaches 80%, and achieving the stacking pressure when the electrolyte ohmic resistance and interface resistance are minimized.

[0297] From the comparison between Examples 22 and 24 and Example 23, it can be seen that controlling the sodium salt to be selected from sodium bis(fluorosulfonyl)imide, the organic solvent to be selected from ethylene glycol dimethyl ether, and the suspended particles to be selected from gas-phase silica or sodium oxide is beneficial to further improve the extrusion strength of the non-Newtonian fluid electrolyte composition when the open circuit voltage reaches zero, to a greater extent improve the average coulombic efficiency of the battery and the number of cycles when the capacity retention rate reaches 80%, and to significantly reduce the expansion rate of the battery when the capacity retention rate reaches 80% and achieve the stacking pressure when the electrolyte ohmic resistance and interface resistance are minimized.

[0298] From the comparison between Example 1 and Examples 25-26, it can be seen that compared with the use of Na(Cu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 )O2 or ZrO2, TiO2 coated Na 2 / 3 Ni 1 / 6 Mn 2 / 3 Cu 1 / 9Mg 1 / 18 Using O2 as the positive electrode active material and Na4Fe3(PO4)2P2O7 as the positive electrode active material is more conducive to improving the average coulombic efficiency of the battery and the number of cycles when the capacity retention rate reaches 80%, as well as significantly reducing the expansion rate when the battery capacity retention rate reaches 80% and achieving the stacking pressure when the electrolyte ohmic resistance and interface resistance are minimized.

[0299] From the comparison between Example 25 and Example 26, it can be seen that compared with the use of Na(Cu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 )O2 is used as the positive electrode active material, and ZrO2 and TiO2 coated Na 2 / 3 Ni 1 / 6 Mn 2 / 3 Cu 1 / 9 Mg 1 / 18 O2 as the positive electrode active material is more conducive to improving the average coulombic efficiency of the battery and the number of cycles when the capacity retention rate reaches 80%, and significantly reducing the expansion rate of the battery when the capacity retention rate reaches 80%.

[0300] From the comparison between Example 14 and Example 21, and Example 15 and Example 22, it can be seen that compared with the non-Newtonian fluid electrolyte containing ethylene glycol dimethyl ether organic solvent, the non-Newtonian fluid electrolyte containing N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide ionic liquid has better performance, which is beneficial to increasing the time for the open circuit voltage of the non-Newtonian fluid electrolyte composition to drop to 2 mV after acupuncture and the extrusion strength when the open circuit voltage reaches zero, as well as increasing the number of cycles when the battery capacity retention rate reaches 80%, and reducing the stacking pressure when the electrolyte ohmic resistance and interface resistance are minimized.

[0301] From the comparison of Examples 1, 27 to 34 and Comparative Example 1, it can be seen that, based on the total mass of the non-Newtonian fluid electrolyte composition, the mass content of the electrolyte salt is 5% to 20%, the mass content of the ionic liquid is 20% to 60%, the mass content of the polymer is 0% to 40%, and the mass content of the suspended particles is greater than 0 and less than or equal to 20%, which is beneficial to increasing the time for the open circuit voltage of the non-Newtonian fluid electrolyte composition to drop to 2 mV after acupuncture and the extrusion strength when the open circuit voltage reaches zero, as well as increasing the average coulombic efficiency of the battery and the number of cycles when the capacity retention rate reaches 80%, reducing the expansion rate of the battery when the capacity retention rate reaches 80%, and achieving the stacking pressure when the electrolyte ohmic resistance and interface resistance are minimized.

[0302] From the comparison of Examples 18, 25-26 and Comparative Examples 7-9, it can be seen that the non-Newtonian fluid electrolyte composition is suitable for a variety of different positive electrode materials. Compared with batteries with liquid electrolytes of similar composition, it can effectively suppress the gas production of the battery through high viscosity, thereby improving the cycle performance of the battery, especially effectively improving the cycle performance of the positive electrode layered oxide at high voltage.

[0303] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and within the scope of the technical solution of the present application, embodiments having substantially the same structure as the technical concept and exerting the same effects are all included in the technical scope of the present application. In addition, within the scope of the subject matter of the present application, various modifications that can be conceived by those skilled in the art to the embodiments, and other methods constructed by combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. An electrolyte composition, characterized in that The electrolyte composition is a non-Newtonian fluid electrolyte composition.

2. The electrolyte composition according to claim 1, characterized in that After the electrolyte composition is stirred by rotating a 62# or 64# rotor of a Dveslvtjo rotary viscosity tester at a speed of 12 rpm for 10 seconds at 25° C., the viscosity of the electrolyte composition is 1000 mPa·s to 50000 mPa·s.

3. The electrolyte composition according to claim 1, characterized in that After the electrolyte composition is stirred by a Dveslvtjo rotary viscosity tester 62# or 64# rotor at a speed of 12 rpm for 10 minutes at 25°C, the viscosity of the electrolyte composition increases by more than 100 mPa·s compared with the viscosity after testing for 10 seconds under the same conditions.

4. The electrolyte composition according to any one of claims 1 to 3, characterized in that The loss factor of the non-Newtonian fluid electrolyte composition after mechanical thixotropy decreases by more than 10% compared with the loss factor before mechanical thixotropy.

5. The electrolyte composition according to any one of claims 1 to 3, characterized in that The non-Newtonian fluid electrolyte composition comprises one of an organic solvent and an ionic liquid, an electrolyte salt, and suspended particles.

6. The electrolyte composition according to any one of claims 1 to 5, characterized in that The non-Newtonian fluid electrolyte composition also includes a polymer.

7. The electrolyte composition according to claim 5 or 6, characterized in that The electrolyte salt comprises a sodium salt, and the sodium salt comprises one or more of sodium chloride, sodium bromide, sodium nitrate, sodium perchlorate, sodium hexafluorophosphate, sodium acetate, sodium trifluoroacetate, sodium trifluoromethylsulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide, and optionally comprises one or more of sodium trifluoromethylsulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide.

8. The electrolyte composition according to any one of claims 5 to 7, characterized in that The organic solvent comprises one or more of an ether organic solvent, an ester organic solvent, and a sulfur-containing organic solvent, and comprises one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, fluoroethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, and dimethyl sulfoxide, and optionally comprises ethylene glycol dimethyl ether.

9. The electrolyte composition according to any one of claims 5 to 8, characterized in that The ionic liquid comprises one or more of 1-butyl-3-methylimidazole chloride, 1-alkyl-3-methylimidazole tetrafluoroborate, N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide, 5-azonia spiro[4,4]nonane hexafluorophosphate, trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide, and tetrabutylphosphine hexafluorophosphate, and optionally comprises one or more of N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide and trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide.

10. The electrolyte composition according to any one of claims 6 to 9, characterized in that The polymer includes polyethylene oxide, polyethylene glycol, polyvinyl pyrrolidone, polymethyl methacrylate, polyvinylidene fluoride, polyvinyl alcohol, polyacrylamide, and optionally includes one or more of polyethylene oxide and polyethylene glycol.

11. The electrolyte composition according to any one of claims 5 to 10, characterized in that The suspended particles include one or more of fumed silica, aluminum oxide, sodium oxide, lithium oxide, sodium fluoride, lithium fluoride, and polyurethane, and optionally include one or more of fumed silica, sodium oxide, and lithium oxide.

12. The electrolyte composition according to any one of claims 5 to 11, characterized in that The electrolyte salt comprises one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide; the organic solvent comprises ethylene glycol dimethyl ether; the ionic liquid comprises one or more of N-alkyl-N-methylpiperidine bis(trifluoromethanesulfonyl)imide and trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide; the polymer comprises one or more of polyethylene oxide and polyethylene glycol; and the suspended particles comprise one or more of fumed silica, sodium oxide, and lithium oxide.

13. The electrolyte composition according to any one of claims 5 to 12, characterized in that The electrolyte salt includes one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide; the organic solvent includes ethylene glycol dimethyl ether; and the suspended particles include one or more of fumed silica, sodium oxide, and lithium oxide.

14. The electrolyte composition according to any one of claims 6 to 12, characterized in that The electrolyte salt comprises one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide; the organic solvent comprises ethylene glycol dimethyl ether; the polymer comprises one or more of polyethylene oxide and polyethylene glycol; and the suspended particles comprise one or more of fumed silica, sodium oxide, and lithium oxide.

15. The electrolyte composition according to any one of claims 5 to 12, characterized in that The electrolyte salt comprises one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide; the ionic liquid comprises one or more of N-alkyl-N-methylpiperidinium bis(trifluoromethanesulfonyl)imide and trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide; and the suspended particles comprise one or more of fumed silica, sodium oxide, and lithium oxide.

16. The electrolyte composition according to any one of claims 6 to 12, characterized in that The electrolyte salt comprises one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide; the ionic liquid comprises one or more of N-alkyl-N-methylpiperidine bis(trifluoromethanesulfonyl)imide and trihexyl(tetradecyl)phosphine bis(trifluoromethanesulfonyl)amide; the polymer comprises one or more of polyethylene oxide and polyethylene glycol; and the suspended particles comprise one or more of fumed silica, sodium oxide, and lithium oxide.

17. The electrolyte composition according to any one of claims 6 to 16, characterized in that Based on the total mass of the non-Newtonian fluid electrolyte composition, the mass content of the electrolyte salt is 5% to 20%, the mass content of the organic solvent is 20% to 60%, the mass content of the ionic liquid is 20% to 60%, the mass content of the polymer is 0% to 40%, and the mass content of the suspended particles is greater than 0 and less than or equal to 20%.

18. The electrolyte composition according to any one of claims 1 to 17, characterized in that The non-Newtonian fluid electrolyte composition has an extrusion strength of 35 kN to 200 kN.

19. A secondary battery, characterized in that: The invention comprises a positive electrode sheet and the electrolyte composition according to any one of claims 1 to 18.

20. The secondary battery according to claim 19, characterized in that: The secondary battery is a sodium metal battery.

21. The secondary battery according to claim 19 or 20, characterized in that: The secondary battery is a negative electrode-free sodium battery.

22. The secondary battery according to any one of claims 19 to 21, characterized in that: The positive electrode sheet includes a positive electrode active material, wherein the positive electrode active material includes at least one of a transition metal layered oxide, a polyanion compound and a Prussian blue compound, including NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2、Na(Cu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 )O2、Na 2 / 3 Ni 1 / 6 Mn 2 / 3 Cu 1 / 9 Mg 1 / 18 O2, Na4Fe3(PO4)2P2O7, NaFePO4, Na3V2(PO4)3, Na 1.9 One or more of CoFe(CN)6, Na2NiFe(CN)6, NaMnFe(CN)6.

23. The secondary battery according to claim 22, characterized in that: The surface of the positive electrode active material has a coating layer, and the coating layer includes one or more of carbon material, ZrO2, TiO2, polyaniline, polypyrrole, poly(3,4-ethylenedioxythiophene), aluminum oxide, zinc oxide, titanium oxide, zirconium oxide, magnesium oxide, silicon oxide, lanthanum oxide, sodium fluoride, lithium fluoride and aluminum fluoride, and the carbon material includes one or more of amorphous carbon, graphite and graphene.

24. A battery module, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 19 to 23.

25. A battery pack, characterized in that: The invention comprises the secondary battery according to any one of claims 19 to 23 or the battery module according to claim 24.

26. An electrical device, characterized in that: The invention comprises at least one of the secondary battery according to any one of claims 19 to 23, the battery module according to claim 24, and the battery pack according to claim 25.

Citation Information

Cited By

  • Thixotropic colloidal gel electrolyte driven by mechanical force as well as preparation method and application of thixotropic colloidal gel electrolyte

    CN121054785A